2013
DOI: 10.1111/cea.12168
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of histone acetylases and deacetylases in inflammatory phenotypes of asthma

Abstract: Neutrophilic airway inflammation is associated with increased HAT and reduced HDAC activity in blood monocytes, demonstrating further systemic manifestations relating to the altered inflammatory gene transcription profile of neutrophilic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 43 publications
3
43
1
Order By: Relevance
“…Asthma is commonly associated with enhanced STAT6 and Ige gene expression that are linked to an increase in HAT activities and decrease in HDAC activities (Gunawardhana et al, 2014;Li et al, 2014). Consistent with these studies, our data confirmed the association of hyperacetylation of histone H3 with asthma (Fig.…”
Section: Acetylation Of H3k9 Associated With Asthma In Il-4/stat6 Patsupporting
confidence: 91%
“…Asthma is commonly associated with enhanced STAT6 and Ige gene expression that are linked to an increase in HAT activities and decrease in HDAC activities (Gunawardhana et al, 2014;Li et al, 2014). Consistent with these studies, our data confirmed the association of hyperacetylation of histone H3 with asthma (Fig.…”
Section: Acetylation Of H3k9 Associated With Asthma In Il-4/stat6 Patsupporting
confidence: 91%
“…Acetylation of histones by transcriptional coactivator HAT leads to chromatin opening for inflammatory gene transcription. It has been reported that the total HAT/HDAC activity ratio is elevated in lungs from severe asthmatics (29). In LPS/IFN-g-treated mouse lungs, we observed a significant increase in total HAT/HDAC activity ratio.…”
Section: Andrographolide Restores Steroid Sensitivity To Block Lps/ Isupporting
confidence: 57%
“…Intact HDAC2 function is indispensable in mediating the transrepression action of steroids to modulate transcriptional activity of NF-kB and AP-1 (22). Elevated HAT activity and impaired HDAC2 protein expression and activity have been reported in lung tissues, alveolar macrophages, and PBMCs from COPD and severe asthma patients (29,44,45). In the present study, we observed a major drop in nuclear HDAC2 level and total HDAC activity and an increase of the total HAT/HDAC activity ratio upon LPS/IFN-g stimulation, which might be responsible for LPS/IFN-g-induced steroid insensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found that in neutrophilic asthma, there was increased HAT and decreased HDAC activity in isolated PBMCs. However, there were no differences in the expression levels of the HATs p300, KAT2B, cAMP response element-binding protein-binding protein or the HDACs HDAC1, HDAC2 or HDAC3, which could indicate differences in activity due to post-translational effects [46]. More recently, it has been identified that acetylation of histone H3 lysine 18 (H3K18) is elevated in asthma epithelium compared with healthy subjects [47], which is in line with a shift toward increased HAT activity.…”
mentioning
confidence: 82%